CMA 101 - Medical Terminology & Body Systems 1 - Linn Benton Virtual College (2018)
Medical Terminology and Body Systems I prepares you to use appropriate medical terminology to identify the structural organization of the body, identify body systems, and describe body special orientation. You will identify the normal function of each body system. You will identify word parts and abbreviations as they relate to body systems. This course has 4 Credit Units that will assist you in learning the course objectives.